Repeated Aspergillus isolation in respiratory samples from non-immunocompromised patients not selected based on clinical diagnoses: colonisation or infection? - Barberan Jose; Alcazar Bernardino; Malmierca Eduardo; Garcia de la Llana Francisco; Dorca Jordi; del Castillo Daniel; Villena Victoria; Hernandez-Febles Melissa; Garcia-Perez Francisco-Javier; Granizo Juan-Jose; Gimenez Maria-Jose; Aguilar Lorenzo (BMC Infectious Diseases, 2012)
Abstract Background Isolation of Aspergillus from lower respiratory samples is associated with colonisation in high percentage of cases, making it of unclear significance. This study explored factors associated with diagnosis (infection vs. colonisation), treatment (administration or not of antifungals) and prognosis (mortality) in non-transplant/non-neutropenic patients showing repeated isolation of Aspergillus from lower respiratory samples. Methods Records of adult patients (29 Spanish hospitals) presenting ≥2 respiratory cultures yielding Aspergillus were retrospectively reviewed and categorised as proven (histopathological confirmation) or probable aspergillosis (new respiratory signs/symptoms with suggestive chest imaging) or colonisation (symptoms not attributable to Aspergillus without dyspnoea exacerbation, bronchospasm or new infiltrates). Logistic regression models (step–wise) were performed using Aspergillosis (probable + proven), antifungal treatment and mortality as dependent variables. Significant (p < 0.001) models showing the highest R2 were considered. Results A total of 245 patients were identified, 139 (56.7%) with Aspergillosis. Aspergillosis was associated (R2 = 0.291) with ICU admission (OR = 2.82), congestive heart failure (OR = 2.39) and steroids pre-admission (OR = 2.19) as well as with cavitations in X-ray/CT scan (OR = 10.68), radiological worsening (OR = 5.22) and COPD exacerbations/need for O2 interaction (OR = 3.52). Antifungals were administered to 79.1% patients with Aspergillosis (100% proven, 76.8% probable) and 29.2% colonised, with 69.5% patients receiving voriconazole alone or in combination. In colonised patients, administration of antifungals was associated with ICU admission at hospitalisation (OR = 12.38). In Aspergillosis patients its administration was positively associated (R2 = 0.312) with bronchospasm (OR = 9.21) and days in ICU (OR = 1.82) and negatively with Gold III + IV (OR = 0.26), stroke (OR = 0.024) and quinolone treatment (OR = 0.29). Mortality was 78.6% in proven, 41.6% in probable and 12.3% in colonised patients, and was positively associated in Aspergillosis patients (R2 = 0.290) with radiological worsening (OR = 3.04), APACHE-II (OR = 1.09) and number of antibiotics for treatment (OR = 1.51) and negatively with species other than A. fumigatus (OR = 0.14) and aspergillar tracheobronchitis (OR = 0.27). Conclusions Administration of antifungals was not always closely linked to the diagnostic categorisation (colonisation vs. Aspergillosis), being negatively associated with severe COPD (GOLD III + IV) and concomitant treatment with quinolones in patients with Aspergillosis, probably due to the similarity of signs/symptoms between this entity and pulmonary bacterial infections.